Enhanced Electrocatalytic Activity in GaSe and InSe Nanosheets: The Role of Surface Oxides. (11th September 2020) - D'Olimpio, Gianluca; Nappini, Silvia; Vorokhta, Mykhailo; Lozzi, Luca; Genuzio, Francesca; Menteş, Tevfik Onur; Paolucci, Valentina; Gürbulak, Bekir; Duman, Songül; Ottaviano, Luca; Locatelli, Andrea; Bondino, Federica; et al.
Abstract: Gallium selenide (GaSe) is a van der Waals semiconductor widely used for optoelectronic devices, whose performances are dictated by bulk properties, including band‐gap energy. However, recent experimental observations that the exfoliation of GaSe into atomically thin layers enhances performances in electrochemistry and photocatalysis have opened new avenues for its applications in the fields of energy and catalysis. Here, it is demonstrated by surface‐science experiments and density functional theory (DFT) that the oxidation of GaSe into Ga2 O3, driven by Se vacancies and edge sites created in the exfoliation process, plays a pivotal role in catalytic processes. Specifically, both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are energetically unfavorable in pristine GaSe, due to energy barriers of 1.9 and 5.7–7.4 eV, respectively. On the contrary, energy barriers are reduced concurrently with surface oxidation. Especially, the Heyrovsky step ( H ads  + H +  + e −  → H2 ) of HER becomes energetically favorable only in sub‐stoichiometric Ga2 O2.97 (−0.3 eV/H + ). It is also discovered that the same mechanisms occur for the case of the parental compound indium selenide (InSe), thus ensuring the validity of the model for the broad class of III‐VI layered semiconductors. Abstract : Both hydrogen evolution reaction and oxygen evolution reaction are energetically unfavorable in pristine GaSe and InSe, while energy barriers are reduced concurrently with surface oxidation.